ANALYSIS OF TOTAL MICROBIAL IN MARINATED SCALLOP Gafrarium tumidum DURING COLD STORAGE - Meigy Nelce Mailoa; Johana Tupan; Cindy R. M. Loppies; Bryan Oraplean (Pattimura University, 2017)
This study was conducted to analyze the number of microbes on marinated scallops Gafrarium tumidum during cold storage. The results showed that the number of microbes on the scallops marinated products G. tumidum ranged from1.1 x 102 - 7.4 x 102 cfu/g, so that they meet the SNI 01-2725-1992, the maximum limit of microbial contamination is 5.0 x 105 cfu/g. Total plate count (TPC) value marinated scallops with storage time to 14 days is below the maximum limit is set, so that the marinated of shellfish products G. tumidum still meet microbiological standards and suitable for consumption.